Analysis of the Use of the Budget at the Regional Disaster Management Agency (BPBD) in the Distribution of Goods to Communities Affected by Natural Disasters in Yogyakarta City - Engko, Tiburtius Evanrianus; Rinaldi, Rinaldi (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
Disasters are a series of events that threaten people's lives, caused by environmental damage, high rainfall, and irresponsible community behavior that worsens disaster conditions, especially floods, which often occur in Indonesia. Natural, non-natural, and human factors. Natural factors include: Earthquakes, Tusunami, Losor Land. Non-natural factors include: Forest Fires. This study aims to analyze the use of the budget by the Regional Disaster Management Agency (BPBD) in distributing goods to people affected by natural disasters in Yogyakarta. The approach used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study show that budget management in BPBD has been carried out in accordance with applicable regulations, but faces several obstacles such as limited funds, complex bureaucracy, and time mismatches between budget planning and disaster events. The distribution strategy of goods is carried out through the identification of needs in the field, procurement based on applications, as well as documentation and evaluation in a transparent and accountable manner. SWOT analysis is also used to identify strengths, weaknesses, opportunities, and threats in the use of the BPBD budget. This study concludes that the effectiveness and efficiency of budget use are greatly influenced by an adaptive planning system and good inter-agency coordination. These findings are expected to be strategic inputs for improving financial governance in disaster management at the regional level.